2020
DOI: 10.1186/s41927-020-00143-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Initiated Follow-Up (PIFU) as reorganized support for increased patient involvement – focus group discussions among patients’ with inflammatory arthritis

Abstract: Background: Inflammatory Arthritis is characterized by lifelong medical treatment and an unpredictable trajectory because of the fluctuating nature of the diseases. Proactive disease management is recommended, which includes close monitoring of disease activity that traditionally has been ensured by outpatient visits to rheumatologists at various fixed intervals. Internationally, there is a growing interest in how healthcare systems can be more flexible, individual-oriented and increasingly involve patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This is a source of inefficiency and frustration currently in the UK [ 38 ], and addressing it would greatly improve patient empowerment, satisfaction and self-management. Greater use of patient-initiated follow-up (PIFU) [ 39 ] may also reduce existing inefficiencies and sub-optimal care from the current dominant model of reviewing rheumatology patients according to timescales rather than disease activity. However, this study has demonstrated that a move towards further PIFU urgently requires improved administrative systems in some rheumatology departments to ensure a prompt, appropriate response to the vast increase in patient-initiated contact.…”
Section: Discussionmentioning
confidence: 99%
“…This is a source of inefficiency and frustration currently in the UK [ 38 ], and addressing it would greatly improve patient empowerment, satisfaction and self-management. Greater use of patient-initiated follow-up (PIFU) [ 39 ] may also reduce existing inefficiencies and sub-optimal care from the current dominant model of reviewing rheumatology patients according to timescales rather than disease activity. However, this study has demonstrated that a move towards further PIFU urgently requires improved administrative systems in some rheumatology departments to ensure a prompt, appropriate response to the vast increase in patient-initiated contact.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, parts of the validated questionnaire used (RAPID3) seemed outdated or not clear enough for many patients, highlighting the need for continuous reevaluation. A PIFU-based strategy has been demonstrated to be safe, yet previous qualitative research revealed that it also causes patient anxiety [27] due to more patient responsibility [33] and implementation can be facilitated by increasing the responsiveness of the system and the system incorporating regular disease monitoring. Overall, we believe a safety net in form of planned semi-automated asynchronous monitoring provides a balanced risk-benefit ratio [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous works on this subject, while finding patients appropriately knowledgeable to monitor their own health status, found high levels of confusion as to the distribution of responsi-bility between themselves and their clinician. 12 Consequently, care must first be taken to delineate these responsibilities, and provide greater community support to those with increased clinical complexities.…”
Section: Key Considerationsmentioning
confidence: 99%